Mouse beta 2-microglobulin cDNA clones: a screening procedure for cDNA clones corresponding to rare mRNAs. - Parnes, J R (1981)
We have isolated three cDNA clones for beta 2-microglobulin, the small subunit of the major histocompatibility antigens. beta 2-Microglobulin makes up less than 0.1% of mouse liver protein, and its mRNA is approximately 0.03% of liver poly(A)+ mRNA. The cDNA clones were identified by screening 1400 cDNA clones made from 9--10S mouse liver poly(A)+ mRNA. The procedure for screening the cDNA clones involved binding pooled plasmid DNA to nitrocellulose filters and testing the ability of each filter to select beta 2-microglobulin mRNA. The filter-selected mRNAs were assayed for their ability to direct the synthesis of beta 2-microglobulin in translation reactions in vitro. The isolated clones were shown by nucleotide sequence analysis to encode beta 2-microglobulin. The positive-selection--hybridization assay has been modified to facilitate the screening of large numbers of cDNA clones, and the modified assay should allow the isolation of cDNAs corresponding to any mRNA whose in vitro translation products can be immunoprecipitated. These modifications are of particular value in the isolation of cDNA clones corresponding to rare species of mRNA.